Lighting - D C Pritchard (Longman, 1996)
The book is long-establishedas the standard work for the teaching of light design and application. It fully complies with 1994 CIBSE lighting code and reflects new standards for road lighting; covers both interior and exterior lighting; contains sufficient data to solve most lighting design calculations; incorporates new material on lighting different types of interior; includes worked examples throughout to support key concepts